Sensory Components of Fruits and Berries - Pochitskaya I.; Roslyakov Y.; Komarova N.; Roslik V. (Техника и технология пищевых производств, 2019)
The research featured consumer properties of 18 varieties of apples, 12 varieties of pears, and 6 varieties of strawberries grown in the Republic of Belarus. The research objective was to study the sensory component composition of apples, pears, and strawberries to select varieties with the best consumer properties. Hexylacetate was detected in Charovnitsa, Zaslavskoye, Belarusian Sinap, and Pamyat Sikory apples. As for the pear varieties, Alesya, Belan, and Krasavita were found to contain butylbutanoate and hexylbutanoate. In all the samples of fresh pears, aroma-forming esters were mainly represented by hexylacetate and butyl acetate. Pears that reached full ripeness contained esters of unsaturated acids that are responsible for a characteristic pear flavor: methyl 2.4-decadienoate and two isomers of (cis-, trans-) ethyl-2.4-decadienoate. All the samples of strawberry contained linalool, which gives a floral flavor. Its quantity differed according to the variety: from 0.4% (Rusish variety) to 4.53% (Alpha variety). The apple varieties of Pamyat Kovalenko, Krasavita, and Dyayment had a high content of sugars (≥ 10%). Charovnitsa, Belana, and Zorka had a low acidity and can be recommended for the production of juice products for children. All the studied varieties of pears had a low sugar content (about 7%) and organic acids (≤ 0.3%), which also makes them suitable for children. The average acid content for strawberry was 9.1 g/kg, while the predominant acid was citric. However, Belarusian strawberries contained less sugar than stated in the databases, an average of 52.5 g/kg. Belana, Dyayment, Zorka, and Charovnitsa apples and Pamyat Yakovleva pears demonstrated a high sugar-acid index and the most harmonious taste. Garden strawberries had a low sugar-acid index value, not more than 6.2. The samples revealed various amounts of catechins, phenolic acids, flavonols, and anthocyanins. The obtained data on the component composition of 18 varieties of apples, 12 varieties of pears, and 6 varieties of garden strawberries of the B elarusian selection can serve as a marker of the authenticity of products by comparing with the existing database of basic quality indicators and the composition of raw materials.